Proximal spleno-renal shunt with retro-aortic left renal vein in a patient with extra-hepatic portal vein obstruction: first case report - Jain, Sundeep (BMC Surg, 2017)
BACKGROUND: Presence of retro-aortic left renal vein poses special challenge in creating spleno-renal shunt potentially increasing the chance of shunt failure. The technical feasibility and successful outcome of splenectomy with proximal spleno-renal shunt (PSRS) with retro-aortic left renal vein is presented for the first time. The patient was treated for portal hypertension and hypersplenism due to idiopathic extra-hepatic portal vein obstruction. CASE PRESENTATION: A twenty year old male suffering from idiopathic extra-hepatic portal vein obstruction presented with bleeding esophageal varices, portal hypertensive gastropathy, asymptomatic portal biliopathy and symptomatic hypersplenism. As variceal bleeding did not respond to endoscopic and medical treatment, surgical portal decompression was planned. On preoperative contrast enhanced computed tomography retro-aortic left renal vein was detected. Splenectomy with proximal splenorenal shunt with retro-aortic left renal vein was successfully performed by using specific technical steps including adequate mobilisation of retro-aortic left renal vein and per-operative pressure studies. Perioperative course was uneventful and patient is doing well after 3 years of follow up. CONCLUSIONS: PSRS is feasible, safe and effective procedure when done with retro-aortic left renal vein for the treatment of portal hypertension related to extra-hepatic portal vein obstruction provided that attention is given to key technical considerations including pressure studies necessary to ensure effective shunt. Present case provides the first evidence that retro-aortic left renal vein can withstand the extra volume of blood flow through the proximal shunt with effective portal decompression so as to treat all the components of extra-hepatic portal vein obstruction without causing renal venous hypertension.